A retrospective analysis of results of anterior interbody fusion with vertical cylindrical mesh implants - Barysh, Oleksandr; Buznytsky, Ruslan (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2013)
Results of the surgical treatment of 10 men with diseases and damages of the cervical spine, who underwent anterior interbody fusion with vertical cylindrical mesh implants without any ventral stabilization with plates, were analysed. Prolapses of the grafts into the vertebral bodies, clinically significant in 30 %, were revealed in 100 % of cases. Mechanisms of changing in the position of these constructions and violation of relationships between the stabilized vertebrae during the postoperative period were revealed.